Methanol preservation of filamentous cyanobacteria for molecular and morphological studies - Churro, Catarina (2018)
This study intends to evaluate the application of methanol fixation in the preservation of viable DNA for PCR reactions and also preserve cell morphology for microscopic studies in filamentous cyanobacteria.